Antinociceptive mechanisms of oleuropein from Olea europaea L. fruits : An in vivo and in silico study - Hidayat Ur, Rahman; Muhammad Hamdi, Mahmood; Najm Us, Sama; Mohd Razip, Asaruddin; Mohammed Safwan, Ali Khan (Biome Scientia Sdn Bhd., 2022)
In recent years, pain has been a major source of concern. It is usually treated with nonsteroidal anti-inflammatory drugs and opioid analgesics, which come in various forms. The adverse effects of these drugs include gastrointestinal bleeding, peptic ulcers, renal failure, cardiovascular difficulties, increased treatment costs, and severe economic losses. Consequently, the search for the ideal painkiller continues. Recent emphasis has been placed on discovering safe and effective drugs derived from natural sources. Olives are among the most important natural resources in the Middle East. Olive (Olea europaea L.), a member of the Oleaceae family, is abundant and widely available, and humans use its fruits and oil. Olive contains flavonoids, secoiridoids, glycosides, phenolic compounds such as tyrosol and its derivatives, galactolipids, triacylglycerols, and fatty acids. Oleuropein is one of the principal olive components that has powerful anti-inflammatory properties. A recent study indicates that oleuropein may be used to treat cancer, inflammation, neurological and cardiovascular disorders. In a recent study, oleuropein-rich extract demonstrated antinociceptive activity in an acetic acid-induced writhing model. However, the mechanisms are still unreported. This led us to design the present investigation to unravel the molecular mechanisms in the antinociceptive action of oleuropein.